Apparent bacteriophage-binding region of an Escherichia coli K-12 outer membrane protein. - Cole, S T (1983)
The 325-residue OmpA protein is one of the major outer membrane proteins of Escherichia coli. It serves as the receptor for several T-even-like phages and is required for the action of certain colicins and for the stabilization of mating aggregates in conjugation. We have isolated two mutant alleles of the cloned ompA gene which produce a protein that no longer functions as a phage receptor. Bacteria possessing the mutant proteins were unable to bind the phages, either reversibly or irreversibly. However, both proteins still functioned in conjugation, and one of them conferred colicin L sensitivity. DNA sequence analysis showed that the phage-resistant, colicin-sensitive phenotype exhibited by one mutant was due to the amino acid substitution Gly leads to Arg at position 70. The second mutant, which contained a tandem duplication, encodes a larger product with 8 additional amino acid residues, 7 of which are a repeat of the sequence between residues 57 and 63. In contrast to the wild-type OmpA protein, this derivative was partially digested by pronase when intact cells were treated with the enzyme. The protease removed 64 NH2-terminal residues, thereby indicating that this part of the protein is exposed to the outside. It is argued that the phage receptor site is most likely situated around residues 60 to 70 of the OmpA protein and that the alterations characterized have directly affected this site.